Hukum Islam: Sebuah Konsep dan Urgensinya - N, Nurfadilah; Rahman, Abd.; Gassing, Qadir (Media Hukum Indonesia (MHI), 2026)
Islamic law is a set of rules established by Allah SWT to serve as a guide for humans in living their lives. These rules are sourced from the Quran, Hadith, ijma' and qiyas (consensus), which regulate various aspects of human life, both individual and social. As a manifestation of sharia, Islamic law emphasizes not only the formal legal aspect but also the moral and spiritual dimensions that guide the community in achieving prosperity in this world and the hereafter. This article discusses the basic concepts of Islamic law, including its definition, sources, objectives, characteristics, and urgency in contemporary life. By exploring the role of Islamic law in establishing justice, maintaining social order, and addressing the challenges of modernity, this paper demonstrates that Islamic law has universal relevance, not only for Muslims but also in its contribution to humanitarian values globally